Development and Validation of Vehicle Adaptability Testing in Australia - Yin, Zhenhua; Zhu, Wei; Li, Wei (International Journal of Mechanical and Electrical Engineering, 2025)
This study systematically analyzed the special requirements of the Australian market for vehicle adaptability. Firstly, the unique climate environment of Australia (extreme high temperatures, sandstorms, high humidity), road traffic characteristics (narrow lanes, complex signs, frequent roundabouts), and user usage habits (widespread use of trailers, CarPlay dependence, etc.) were elaborated in detail. Secondly, by comparing the differences between China and Australia in environmental testing standards, traffic regulations, and user needs, the shortcomings of the existing testing system in China in dealing with UV aging, dynamic speed limit sign recognition, and right-hand drive human-machine interaction were revealed. Finally, targeted development suggestions were proposed, including verification of special operating conditions (roundabout+ speed bump), optimization of charging compatibility, and cooperation with local operators for adaptive development. The research provides a systematic testing and verification method reference for car companies to enter the Australian market.